Validation of Simulation Codes for Nuclear Imaging Using Digital Phantoms - Kikuchi, Akihiro; Yamaki, Noriyasu; Matsutomo, Norikazu; Ito, Toshimune; Shirakawa, Seiji; Tsushima, Hiroyuki; Ichikawa, Hajime; Ljungberg, Michael; Nosaka, Hiroki; Okuda, Koichi (Japanese Journal of Radiological Technology, 2021)
Validation study of simulation codes was performed based on the measurement of a sphere phantom and the National Electrical Manufacturers Association (NEMA) body phantoms. SIMIND and Prominence Processor were used for the simulation. Both source and density maps were generated using the characteristics of 99mTc energy. A full width at half maximum (FWHM) of the sphere phantom was measured and simulated. Simulated recovery coefficient and the background count coefficient of variation were also compared with the measured values in the body phantom study. When the two simulation codes were compared with actual measurements, maximum relative errors of FWHM values were 3.6% for Prominence Processor and -10.0% for SIMIND. The maximum relative errors of relative recovery coefficients exhibited 11.8% for Prominence Processor and -2.0% for SIMIND in the body phantom study. The coefficients of variation of the SPECT count in the background were significantly different among the measurement and two simulation codes. The simulated FWHM values and recovery coefficients paralleled measured results. However, the noise characteristic differed among actual measurements and two simulation codes in the background count statistics.